Beyond the Façade: layering downtown spillover investment. Issue 2 (15th March 2021) - Gibson, Huston; Zurcher, Micky; Wisemiller, Tash
ABSTRACT: In a time when funding for small communities is limited, an analysis of investment strategy is critical. Façade improvement grant programs are thought to spur spillover of both direct and indirect investment in downtown districts by leveraging built capital and harnessing a sense of place. Through case study, with interviews and observational analysis, we empirically analyze this phenomenon in three U.S. communities in the state of Montana; Helena, Kalispell, and Anaconda. Findings show that direct public-private investment through downtown façade grants, administered by downtown-focused organizations in accordance with long-range plans and visions, leverages positive indirect spin-off via supplementary privately initiated renovations and building maintenance. This implies that strategic downtown investment through façade grants generates a multiplier effect, creating layers of return on investment.